(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was carried out for the studying CYP19 gene polymorphism and its effect in concentrations of estrogen and progesterone in local ectopic ewes. Blood samples were collected from ewes in the fields of Husseiniya on the Najaf / Karbala road. In terms of the field side, estrogen concentrations The highest concentration of progesterone (0.5893 ng / ml) and the lowest concentration (ng / ml0.1302) was the isolation of the genetic bundle For the third CYP19 genome of 140 bp and the determination of the structures Genotype). The genotype of the CYP19 gene in the sample of local ewes was 6.25%, 31.25%, and 62.50% for the TT, TC and CC sequences in the sequence. Concentration measurement results Estrogen had a significant effect on the level of P (0.05) in the genotype TT and TC (15,5745,15,4617) respectively, compared with the CC model (14.2362), while there was no significant difference between the TT and TC models. Progesterone significantly exceeded the P00.05 probability level in the Ur model (0.47770) on the genotype TT and CC (0.3288,0.2469). The progesterone concentration of the TT genotype decreased significantly compared with TC and CC. The study found that the genetic makeup of the gene CYP19 on the genetic structures of TT and CCW and the polymorphism of CYP19 gene in Exon3 had a significant effect on estrogens and progesterone concentrations. Individuals carrying the genetic makeup of the gene CYP19 were superior to the TT and CC structures in estrogen and progesterone concentrations.